2006
DOI: 10.1002/dvdy.20823
|View full text |Cite
|
Sign up to set email alerts
|

A new serine/threonine protein kinase,Omphk1, essential to ventral body wall formation

Abstract: Here, we report a new serine/threonine protein kinase of the SNF1 subfamily Omphk1. Two Omphk homologues exist in each vertebrate species, and one homologue exists in Drosophila and Caenorhabditis elegans; the kinase domain is highly conserved among these homologues, and several domains are conserved among vertebrate Omphk. Omphk1 expression dynamically changes in the developing central nervous system, is found ubiquitously in epidermis, and is present uniquely in several other tissues. Its expression is also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 29 publications
2
46
0
Order By: Relevance
“…We also performed bioinformatics analysis to determine sequence conservation between these two homologs. The expression patterns we describe are similar to those previously obtained for NUAK1 in wild-type mice embryos using a b Gal fusion protein (Hirano et al, 2006). In the chick, the regionally-restricted expression of NUAK isoforms overlaps.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…We also performed bioinformatics analysis to determine sequence conservation between these two homologs. The expression patterns we describe are similar to those previously obtained for NUAK1 in wild-type mice embryos using a b Gal fusion protein (Hirano et al, 2006). In the chick, the regionally-restricted expression of NUAK isoforms overlaps.…”
Section: Resultssupporting
confidence: 82%
“…Although these genes are mainly expressed in the neuroectoderm in mouse, it has been reported that NUAK1 mutants exhibit no apparent gross brain defects, but do have ventral body wall defects (Hirano et al, 2006). Mice deficient in both NUAK1 and NUAK2 display exencephaly, facial clefting, and spina bifida, suggesting partially redundant activity for these two genes (Ohmura et al, 2012).…”
mentioning
confidence: 99%
“…Also there is experimental mouse evidence showing that teratogen caused apoptosis of the lateral wall musculature is associated with large abdominal wall defects in mice [Wei and Sulik, 1993]. However, it should be kept in mind that there are differences in the early embryology of mouse and human with respect to the relationship of the yolk sac to the embryo and in the process of abdominal wall closure [Hirano et al, 2006]. There are two reasons we have looked to an alternative explanation.…”
Section: What Can Be Summarized and Concluded From An Examination Of mentioning
confidence: 99%
“…There are several animal models that have been referred to as models for human gastroschisis/omphalocele but the animals in fact suffer large ventral wall defects; neither gastroschisis nor true omphalocele [Minsker et al, 1983;Hillebrandt et al, 1998;Hirano et al, 2006;Layne et al, 2001]. The gene Omphk1 is expressed in the epidermis and all tissues of the lateral abdominal wall and in the knockout mouse model there is complete failure of abdominal wall closure [Hirano et al, 2006].…”
Section: What Can Be Summarized and Concluded From An Examination Of mentioning
confidence: 99%
See 1 more Smart Citation